Propriedades vibracionais e ópticas de WSe2 e MoS2: efeitos do número de camadas e da pressão - Sousa, José Hugo de Aguiar (2024)
In this work we present Raman spectroscopy studies under high pressure conditious carried out on samples of tugsten diselenide and molybdenum disulfide in the form of monolayer, trilayer, many layers and bulk. For tugsten diselenide monolayer samples, all first and second order mo des broaden and move to high frequencies with increasing pressure, thus exhibiting monotonic behavior up to pressures of approximately 15 GPa, in which the second order vibrational mo des a whose intensify becomes more pronounced for higher pressure values. By observing the behavior of the ruby, a glass transition of the pressure transmitting medium is observed, which drastically alter the hydrostaticity conditions of the experiment, thus inducing a strain compo nent in the monolayer sample. The increase in intensity of the second order mode, specifically the LA mode, is induced by a structural defect. For the tungsten diselenide bulk sample, we observed that the modes evolve with increasing pressure also in a monotonous and approxima tely linear way, even after the loss of hydrostaticity of the transmitting medium. We observed a break in the degeneracy of the A1g and E2g modes due to differences in responses to increa sing pressure, where it is attributed to a combination of phonons labeled LA(M) +TA(M). For the molybdenum disulfide monolayer sample excited with an energy of 2.33 eV, no significant change is observed up to a pressure of 10 GPa. However, above this value and remarkable incre ase in the LA and 2LA modes is observed as pressure increases. In our work, this enhancement is observed at completely different pressure values in the intenrity to this result is due to the influence of strain induced by the substrate, which in our experiment is of smaller magnitude. We carried out Raman study under resonance conditions near A excitonic transitions by using energy of 1.96 eV varying pressure on monolayer, trilayer and many layer samples of molyb denum disulfide. Our studies show a linear shift for most modes, except for the second order LA(K) + TA(K) and 2LA, whose pressure-dependent frequency is nonlinear. The pressure de pendence of these bands is explained by considering the dispersive scattering process that gives rise to these two modes, where the phonon and exciton energies blue shift as the pressure in creases. Furthermore, the A1g mode resonance in 1L-MoS2 is reached at ∼ 7.0 GPa, while for 3L-MoS2 and many layers of MoS2, occurs at ∼ 3.4 GPa. This difference is attributed to the lower pressure coefficient of the excitonic transition A for 1L-MoS2, compared to 3L-MoS2 and the many layers of MoS2. Our findings constitute an important step towards understanding and controlling the optoelectronic properties of WSe2 and MoS2 through strain/pressure, which are relevant in the design of new flexible electronic devices.